VALIDITAS LEMBAR KERJA MANDIRI PERSIAPAN UJIAN NASIONAL MATEMATIKA TERINTEGRASI PENDEKATAN KONSTRUKTIVISME DILENGKAPI PERMAINAN TEKA TEKI SILANG MODIFIKASI UNTUK SISWA KELAS VI SEKOLAH DASAR - Zakirman,, Syelfia Dewimarni, Lili Rismaini, (RC-INSTITUT, 2018)
Mathematics subjects are one of the subjects included in the national exam (UN). In dealing with the National Examination it takes preparation and lots of practice questions and has complete teaching materials to make it easy to repeat the lesson both independently. But in reality, most students do not have complete questions about the collection of UN materials. Therefore it is designed a teaching material that can increase students' interest in the material and work on practice questions to deal with the National Examination. The purpose of this study was to produce an independent worksheet for the preparation of integrated mathematics national exams constructivism approach equipped with modified crossword puzzles. The development model is the 4D model, Define, Design, Develop and Disseminate. Stage Develop is the development stage to produce independent worksheets for preparation of integrated mathematics national exams. Constructivism approach is equipped with a valid modified crossword puzzle game. Independent worksheets are validated by three experts using the validation sheet. Based on the analysis carried out, the value of the validity of teaching materials in the form of independent worksheets for preparation of integrated mathematics national exams constructivism approach is equipped with a modified crossword puzzle game of 91.87 with very valid criteria. Keywords: Validity of independent worksheets; Elementary School Mathematics National Examination